Efficacy of pancreatic duct stenting to prevent postendoscopic retrograde cholangiopancreatography pancreatitis after covered self‐expandable metal stent deployment. Issue 3 (22nd October 2022) - Toyonaga, Haruka; Hayashi, Tsuyoshi; Yamazaki, Hajime; Hama, Kazuki; Iwano, Kosuke; Nakamura, Risa; Ando, Ryo; Shimizu, Takao; Ishii, Tatsuya; Kin, Toshifumi; Takahashi, Kuniyuki; Katanuma, Akio
Abstract : Objectives: Although covered self‐expandable metal stents (CSEMSs) are associated with the risk of postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis due to pancreatic duct (PD) orifice obstruction, they are often used for biliary drainage treatment in malignant biliary obstruction (MBO). This study aimed to investigate the efficacy of PD stenting in preventing post‐ERCP pancreatitis after CSEMS implantation. Methods: This retrospective cohort study analyzed 554 patients with transpapillary CSEMS for MBO. Patients with noninitial deployment, benign disease, CSEMS deployment above the papilla, surgically altered anatomy, uncovered self‐expandable metal stents, multiple thin self‐expandable metal stents, and unavailable procedure videos were excluded. Logistic regression analysis estimated the association between PD stenting and post‐ERCP pancreatitis incidence. We adjusted for age, sex, pancreatitis history, prophylactic rectal nonsteroidal anti‐inflammatory drug use, naïve papilla, MBO etiology, and prolonged biliary cannulation time. Results: Among 554 patients, 67 (12.1%) experienced post‐ERCP pancreatitis. Post‐ERCP pancreatitis was recorded in 13.7% of patients in the non‐PD stenting and 4.3% in the PD stenting groups. Pancreatic duct stenting was associated with lower risks of post‐ERCP pancreatitis (odds ratio [OR] 0.28; 95% confidence interval [CI] 0.099–0.79; P = 0.028). In multivariable analysis, the association between PD stenting and lower post‐ERCP pancreatitis incidence was consistent (OR 0.19; 95% CI 0.062–0.58; P = 0.0034). Conclusions: Pancreatic duct stenting could reduce the risk of post‐ERCP pancreatitis after CSEMSs.